Challenging management of a child with an expanding pontine cavernous malformation - Efstathios Beys-Kamnarokos; Ioannis Mavridis; Theodossios Birbilis (Elsevier, 2023)
We present a rare neurosurgical entity in a 9-year-old girl who presented with a three-day history of right-sided weakness and numbness. Her parents reported hospitalization six years ago with similar symptoms, due to a probable brainstem cavernous malformation. At that time, she underwent excision of a cortical lesion (probable cavernoma) and conservative management of the brainstem lesion with dexamethasone. Her brain magnetic resonance imaging scan in our hospital revealed a large cavernous malformation protruding into the 4th ventricle, with recent bleeding and mass effect to the pons, as well as another hypothalamic cavernoma. She was conservatively managed with intravenous dexamethasone and discharged home three days later with no deficits, on a tapering scheme of oral dexamethasone and instruction for physiotherapy and evaluation in a radiosurgery center. This case was discussed in our Department's Monthly Interinstitutional Pediatric Neuroscience Meeting. Α possible surgical intervention, if needed in the future, was considered as another option in the armamentarium of the management strategy for this potentially life-threatening lesion. A multidisciplinary approach is particularly helpful in determining the optimal management plan of challenging cases in Pediatric Neurosurgery.